As possíveis relações entre desenvolvimento moral e uso de crack por adolescentes - Souza, Hilton Moreira de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The dependency of psychoactive substances whether licit or illicit, among adolescents is a topic that has aroused much discussion today. One of the psychoactive substance that has caught the attention of authorities and experts, its potential dependence, increasing the number of addicts and speed with which triggers the human degeneration is the crack (a derivative of cocaine - Erythroxylon coca), used via the smoked administration. Understanding the phenomenon of increasing their use requires an analysis of the concepts of addiction throughout history, current research encompassing scientific findings in epidemiology and statistics involving several types of pharmacological substances, and especially the analysis of data related specifically to crack the focus of our theme. In order to contribute to ongoing discussions and offer possible alternatives for effective intervention, especially in schools, we conducted a survey that sought to find evidence of a possible relationship between crack use and moral reasoning. Since our work specifically theoretical nature, we use to reach our goals, assumptions, two researchers in the concept of human morality: Jean Piaget (1994) and Lawrence Kohlberg (1992) both traveling within the proposed cognitive-evolutionary human development. For an understanding of the proposals of these two researchers, we use research to (Lepre, 2005), as guiding thesis of this work. The results presented indicate that adolescents who use crack are very close to a level of moral reasoning pre-conventional and conventional, although it is important to state that more accurate results require further research on the subject, including those involving field research. Yet we can conclude that prevention must go through a dialogue that privileges the moral education as possible means of effective intervention against the use of crack, allowing the construction of autonomy... (Complete abstract click electronic access below)

A dependência de substâncias psicoativas sejam elas ilícitas ou lícitas, entre os adolescentes, é um tema que vem suscitando muitas discussões na atualidade. Uma das substancias psicoativas que vem chamando a atenção das autoridades e dos especialistas, pelo seu potencial de dependência, aumento do número de adictos e rapidez com que deflagra a degeneração humana é o crack (derivado da cocaína - Erythroxylon coca), utilizada através da via de administração fumada. A compreensão do fenômeno do aumento do seu uso exige uma análise sobre os conceitos de dependência química ao longo da história, as atuais pesquisas científicas englobando estatísticas de epidemiologia e descobertas farmacológicas envolvendo vários tipos de substâncias, e principalmente a análise desses dados relacionados especificamente ao crack, foco de nosso tema. Com o objetivo de contribuir para as atuais discussões e oferecer possíveis alternativas para intervenções efetivas, sobretudo no âmbito escolar, realizamos uma pesquisa que procura localizar indícios de uma possível relação entre o uso de crack e o raciocínio moral. Sendo nosso trabalho de cunho especificamente teórico, lançamos mão, para o alcance de nossos objetivos, dos pressupostos de dois pesquisadores da área de conceituação da moralidade humana: Jean Piaget (1994) e Lawrence Kohlberg (1992) ambos transitando dentro da proposta cognitivo-evolutiva do desenvolvimento humano. Para uma compreensão das propostas desses dois pesquisadores, nos valemos da pesquisa de (LEPRE, 2005), como tese norteadora do presente trabalho. Os resultados apontados sinalizam que os adolescentes que fazem uso de crack podem estar muito próximos de um nível de raciocínio moral pré-convencional e convencional, embora seja importante afirmar que resultados mais precisos exigem pesquisas mais aprofundadas sobre o assunto, inclusive envolvendo... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Adolescentes; Crack (Droga); Psicotropicos; Educação moral; Teenagers; Crack (Drug); Psychotropic drugs; Moral education